2023
DOI: 10.3390/su152316316
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Phosphorus Compounds in the Influence Zone Affected by Nuclear Power Plant Water Discharge in the Styr River (Western Ukraine): Case Study

Pavlo Kuznietsov,
Olha Biedunkova,
Yuliia Trach

Abstract: The main causes of surface water pollution with phosphate ions are various human activities. Monitoring the content of phosphorus compounds in surface waters is important for the management of water bodies. Phosphorus is an essential element for the life of flora and fauna, but in excessive amounts it can have a harmful effect on the environment. The inflow of phosphorus compounds into the Styr River (Western Ukraine) occurs as a result of the discharge of cooling water from the Rivne NPP’s cooling water syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The variations observed for the DIS content of the system cooling water of the RNPP ORS are greater than those observed for the make-up water quality, since there is constant make-up and evaporation with concentration [44]. Therefore, the temporal variation is more pronounced in the system cooling water than in the make-up water [45]. Changes in the proportions of make-up water and system cooling water are observed for all the except TH and Σ(Ca 2+ , Mg 2+ ).…”
Section: Indicators Typical LV [6]mentioning
confidence: 79%
“…The variations observed for the DIS content of the system cooling water of the RNPP ORS are greater than those observed for the make-up water quality, since there is constant make-up and evaporation with concentration [44]. Therefore, the temporal variation is more pronounced in the system cooling water than in the make-up water [45]. Changes in the proportions of make-up water and system cooling water are observed for all the except TH and Σ(Ca 2+ , Mg 2+ ).…”
Section: Indicators Typical LV [6]mentioning
confidence: 79%
“…The bene ts of this study are the use of different types of environmental standards and the exploration of students' recall of information about environmental standards and MPC in water bodies. Moreover, the different interpretations of the OPI levels obtained by the different methods of this study include the interpretation of results from 'none' for (3, 4) to 'pure' for (1,2). Students can acquire a systematic approach to the environmental assessment of pollution and avoid ambiguity in the interpretation of results 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Water is widely used to meet human needs for drinking, irrigation, sheries and energy production, and the purpose of its use depends on the quality of the water, making the maintenance of its quality indicators relevant. Water quality is determined by physical, chemical and biological indicators 2 . The relevant documents regulating the impact of water discharges on the environment are the Water Code of Ukraine (WCU) 3 and the Water Framework Directive (WFD) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Although river sediments are known for their ability to absorb some heavy metals and ultimately reduce water pollution, they will also release heavy metals into the water, causing secondary pollution that is difficult to control. In the sediments, the results indicated that potential sources of heavy metals are anthropogenic activities [96] and the weathering of the high-grade metamorphic rocks like amphibolite, gneiss, and granulites rocks dominantly present in the urban reaches of the Ngerengere catchment. In the dry season, high concentration ranges of the major heavy metals in the Ngerengere River sediments were 1.08 ± 0.06 mg/kg, 1.27 ± 0.02 mg/kg, 2.53 ± 0.056 mg/kg, 4.11 ± 0.02 mg/kg, and 0.64 ± 0.01 mg/kg for Cu, Ni, Cr, Zn, and Pb, respectively.…”
Section: Physical Parametersmentioning
confidence: 99%
“…The elevated phosphate concentration at S2 might be attributed to point sources and non-point/diffuse sources, possibly containing both organic and inorganic forms of this element; the water at the sampling station, being a dam with low water velocity, facilitates the gradual settling of suspended solids (SSs) along with particulate phosphorus (PP) [95], and this phenomenon is responsible for eutrophication in surface water. Diffuse sources involve inputs from the leaching of geological rocks and land use, whereas point sources consist of industrial discharge [96]. In surface waters, phosphate and polyphosphate inorganic compounds constitute the prevalent forms of phosphorus, while organic phosphorus arises from the life processes and decay of aquatic organisms, along with human activities that contribute to phosphorus release [97].…”
Section: Nutrient Loading In Water and Sedimentsmentioning
confidence: 99%